Peningkatan Branding Sekolah Melalui Pelatihan Public Speaking pada SMP Islam Plus Nihadul Qulub Ungaran Kab. Semarang - Nikmatuniayah Nikmatuniayah; Resi Yudhaningsih; Aditya Rizqi Senoji; Siti Mutmainah; Lilis Mardiana A; M Asrori; Moh Haris; Sri Hardiningsih; Yusuf Hendrawanto; Pandiya Pandiya; Toni Hartono (Universitas Pahlawan Tuanku Tambusai, 2026)
The main objective of this program is to improve the quality of school branding through national and international public speaking training. The purpose of this community service is to apply public speaking techniques for teachers in teaching and learning activities, thereby improving school branding through school achievement. The methods used are as follows: (1) socialization and collaboration with administrators, followed by public speaking training for teachers for teaching and learning activities and public speaking for students. (2) mentoring in public speaking practices by creating mass media content and storytelling in English. After participating in mentoring by the Polines Community Service Team, SMP Plus Nihadul Qulub Ungaran, Semarang Regency, achieved the following targets: (1) School teachers are able to master public speaking for teaching and learning activities. (2) School teachers are able to master public speaking for the general public by creating public video content for mass media. (3) Improving branding for SMP Plus Nihadul Qulub in Semarang Regency.